Pola Komunikasi “Shihab & Shihab” pada Narasi TV dalam Perspektif Etnografi Komunikasi - Fahmi Gunawan; NFN Abbas (Madah: Jurnal Bahasa dan Sastra, 2019)
This study aims to examine the communication patterns of “Shihab & Shihab” on Narasi TV with the episode of "Muslim and Christian Brothers". This study uses a type of qualitative research with ethnographic of communication method. To collect data, observation and documentation were conducted. Data analysis was performed using content analysis from Spradley. The results of the study indicate that tiered clarification system or tabayyun is very important to do in our life, particularly in the revolutional industry 4.0. This phenomenon is reflected in the communication patterns carried out by Najwa Shihab, Quraish Shihab, and Priest Budi in Narasi TV. Ethnography of communication well-known as SPEAKING by Hymes in the form of settings, participants, ends, acts, keys, instruments, norms, and genres are the reasons why the communication pattern uses a tiered clarification system.AbstrakPenelitian ini bertujuan untuk mengkaji pola komunikasi “Shihab & Shihab” pada Narasi TV episode “Muslim dan Nasrani Bersaudara”. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan etnografi komunikasi. Pengumpulan data dilakukan dengan observasi dan dokumentasi. Analisis data dilakukan dengan menggunakan analisis isi model Spradley. Hasil penelitian menunjukkan bahwa sistem klarifikasi berjenjang terhadap sesuatu sangat penting di dalam kehidupan, terutama di zaman revolusi industri 4.0. Fenomena itu terefleksikan dari pola komunikasi yang dilakukan Najwa Shihab, Quraish Shihab, dan Romo Budi. Etnografi komunikasi SPEAKING Hymes yang berupa setting, partisipant, ends, acts, key, instruments, norm, dan genre menjadi alasan pola komunikasi itu menggunakan sistem klarifikasi berjenjang.